2023
DOI: 10.1108/bpmj-11-2022-0571
|View full text |Cite
|
Sign up to set email alerts
|

Identification and assessment of risks related to digitalization in Indian construction: a quantitative approach

Abstract: PurposeThe purpose of this research article is to investigate the critical risk factors associated with the digitalization impact on the Indian construction industry, as these firm plans to implement digitalization in order to improve their construction management processes.Design/methodology/approachIn this research article, risk factors and dimensions are taken from diverse industries and validated in the construction domain by industry and academic experts. Further, multi-criteria decision-making techniques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 46 publications
(96 reference statements)
0
3
0
Order By: Relevance
“…Xu et al (2023) evaluated regional differences in construction safety performance in China using three-stage DEA analysis to enhance sustainable safety practices (Xu et al 2023). Bajpai et al (2023) identified critical digitalization risks in Indian construction using Fuzzy DANP and Grey TOPSIS for project management (Bajpai et al 2023). Lux et al (2023) proposed using deep learning networks to estimate composition of recycled aggregates for sustainability monitoring in construction (Lux et al 2023).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Xu et al (2023) evaluated regional differences in construction safety performance in China using three-stage DEA analysis to enhance sustainable safety practices (Xu et al 2023). Bajpai et al (2023) identified critical digitalization risks in Indian construction using Fuzzy DANP and Grey TOPSIS for project management (Bajpai et al 2023). Lux et al (2023) proposed using deep learning networks to estimate composition of recycled aggregates for sustainability monitoring in construction (Lux et al 2023).…”
Section: Literature Reviewmentioning
confidence: 99%
“…There is a need for organizations that have completed their [14,17,19,21,[36][37][38] 7/38 digital transformation in the construction digital transformation in the construction industry and will set industry an example for other companies that benefit from the benefits of the transformation. However, since the number of companies involved in the digital transformation process is low, there is a lack of competition and motivation within the sector.…”
Section: Lack Of Competition and Motivation Formentioning
confidence: 99%
“…These professionals analyze potential risks and derive solutions to prevent or mitigate the impact of these pitfalls (Cornwell et al, 2023). Over the past few years, risk management has evolved significantly, playing a crucial role in enabling organizations to anticipate and prepare for risks more effectively (Bajpai et al, 2023). This evolution has placed organizations at a strategic advantage, allowing them to become more resilient and adaptive in the face of uncertainty (Putra et al, 2022).…”
mentioning
confidence: 99%